The Counselor Multicultural Competence: An Exploration Study of Counselor Competence in the Counseling Process - Alfaiz, Alfaiz; Da Costa, Augusto; Yuzarion, Yuzarion; Julius, Andre; Yandri, Hengki; Khairiyah Sari, Azmatul; Hidayat Rafiola, Ryan (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2022)
Many changes in the education system affect the professionality level practiced by counselors. Cultural diversity and acculturation pushed a counselor to be more professional in counseling multicultural skills. This research aims to discover a counselor's skill in multicultural competence that consist of foundation dimension, multicultural dimension, and multicultural counseling. This competency is important and needed in Indonesia as a country with more heterogeny in social, culture, and religion. The research method was used as descriptive quantitative research through the Counselor's Multicultural Competence Scale (CMCS) that was distributed to 100 school counselors in Padang, Indonesia. The result shows that 60 school counselors have a low foundation dimension and multicultural dimension, 50 have low multicultural counseling, and 10 have high three dimensions. This research results recommend a new approach and model for educating and developing a counselor's skills in a multicultural approach to counseling.